PENGEMBANGAN MEDIA LUMAT (LUDO MATEMATIKA) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA FASE C PADA MATERI PECAHAN - Annisa Fitri; Abdul Mujib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop LuMat (Ludo Matematika) learning media to improve the conceptual understanding of mathematics among Phase C students on the topic of fractions. The research employed the Four-D (4D) development model, which includes Define, Design, Develop, and Disseminate stages. The research subjects were 24 fifth-grade students at SD Swasta Kasih Ibu. The instruments used included validity questionnaires, practicality questionnaires, effectiveness questionnaires, as well as pretest and posttest questions to measure the improvement in conceptual understanding. The validation results from media experts showed a score of 96%, categorized as very valid, while material experts gave a score of 78%, categorized as valid. The practicality test indicated that the LuMat media was highly practical for both teachers and students, with an average practicality score of 90.4%. The effectiveness of the media was demonstrated by the increase in students' learning outcomes, with the N-Gain score rising from 0.46 in the first trial to 0.58 in the second trial, which falls into the moderate category. In conclusion, the LuMat media is feasible, practical, effective, and capable of enhancing students’ conceptual understanding in learning fractions.